2015
DOI: 10.1136/bjophthalmol-2015-307238
|View full text |Cite
|
Sign up to set email alerts
|

Vector analysis of astigmatic correction after small-incision lenticule extraction and femtosecond-assisted LASIK for low to moderate myopic astigmatism

Abstract: Our results showed that SMILE offered a less favourable astigmatic correction comparable to femtosecond-assisted LASIK in eyes with low to moderate myopic astigmatism. The alignment of treatment was more variable in SMILE, leading to a lower efficacy compared with LASIK by 3 months postoperatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
78
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 91 publications
(87 citation statements)
references
References 26 publications
7
78
0
2
Order By: Relevance
“…Ivarsen and Hjortdal reported that undercorrection of astigmatism increased with attempted treatment following SMILE16. Undercorrection of astigmatic error has been reported in previous studies comparing SMILE to other corneal refractive surgeries8171819. The CI was very close to 1.0 for SMILE in our cohort, representing accurate astigmatic correction.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Ivarsen and Hjortdal reported that undercorrection of astigmatism increased with attempted treatment following SMILE16. Undercorrection of astigmatic error has been reported in previous studies comparing SMILE to other corneal refractive surgeries8171819. The CI was very close to 1.0 for SMILE in our cohort, representing accurate astigmatic correction.…”
Section: Discussionsupporting
confidence: 83%
“…This emphasizes the importance of treatment alignment for successful correction of astigmatism, in addition to the treatment magnitude. Correction of low astigmatism is particularly a concern because of a higher tendency towards larger axis deviations upon vector analysis81923. The spread of absolute AE was much wider for correction of low astigmatism for both procedures.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Data from various studies suggest that this modality is a safe and effective method to correct varying degrees of myopia, with the advantages of minimum postoperative discomfort and restrictions, less dry eye, and probably better biomechanics compared to LASIK 9,10. Studies comparing the results of astigmatism correction with ReLEx SMILE and LASIK, however, showed better outcomes with LASIK, most likely due to non-availability of iris registration and eye tracker in the current version of the femtosecond laser used for the ReLEx SMILE procedure 11,12. However, similar comparison studies have not been reported between T-ICL and ReLEx SMILE.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously reported that the effect of learning curve could affect the visual and refractive outcomes 17. In our hydroexpression group, there were less residual cylinder, and this could be due to effect of learning curve in head positioning and centration during SMILE, as these were the key factors in SMILE astigmatic correction 6. Nevertheless, in our forceps group period (2014), we already had more than 2 years of experience.…”
Section: Discussionmentioning
confidence: 78%